"All Art is Part of the Same Constellation": A Conversation on Craft and Artistic Practice with Heri Dono. (3rd May 2016) - Romain, Julie
Abstract: In this interview with Heri Dono, the artist discusses his ongoing relationship to craft and traditional art in Indonesia. Dono is an artist who intentionally blurs the boundaries between fine art and craft to subvert artistic conventions. Born in 1960 in Jakarta and raised in Semarang, Central Java, Dono is among a generation of artists who came of age during the politically repressive era of Suharto, also known as the New Order (1966–1998). Dono studied painting at the Indonesian Institute of the Arts (ISI) in Yogyakarta between 1980 and 1987. He dropped out of art school to study the popular form of Javanese shadow puppetry known as wayang kulit, and became a professionally trained storyteller dalang (puppet master). That experience heavily inspired Dono's paintings, sculptures, installations, and performances, enabling him to develop his own personal aesthetic and visual language based on the characters depicted in the wayang . Dono regularly enlists craftsmen as well as untrained members of the local community to participate in his projects as a tool of empowerment. In pieces such as Wayang Legenda (1988) and Kuda Binal (1992), Dono drew upon traditional modes of storytelling and ritual dancing as a subtle form of social critique and political commentary.